Limitations of exome sequencing in detecting rare and undiagnosed diseases. Issue 6 (19th March 2020) - Burdick, Kendall J.; Cogan, Joy D.; Rives, Lynette C.; Robertson, Amy K.; Koziura, Mary E.; Brokamp, Elly; Duncan, Laura; Hannig, Vickie; Pfotenhauer, Jean; Vanzo, Rena; Paul, Michael S.; Bican, Anna; et al.
Abstract: While exome sequencing (ES) is commonly the final diagnostic step in clinical genetics, it may miss diagnoses. To clarify the limitations of ES, we investigated the diagnostic yield of genetic tests beyond ES in our Undiagnosed Diseases Network (UDN) participants. We reviewed the yield of additional genetic testing including genome sequencing (GS), copy number variant (CNV), noncoding variant (NCV), repeat expansion (RE), or methylation testing in UDN cases with nondiagnostic ES results. Overall, 36/54 (67%) of total diagnoses were based on clinical findings and coding variants found by ES and 3/54 (6%) were based on clinical findings only. The remaining 15/54 (28%) required testing beyond ES. Of these, 7/15 (47%) had NCV, 6/15 (40%) CNV, and 2/15 (13%) had a RE or a DNA methylation disorder. Thus 18/54 (33%) of diagnoses were not solved exclusively by ES. Several methods were needed to detect and/or confirm the functional effects of the variants missed by ES, and in some cases by GS. These results indicate that tests to detect elusive variants should be considered after nondiagnostic preliminary steps. Further studies are needed to determine the cost‐effectiveness of tests beyond ES that provide diagnoses and insights to possible treatment.